2022
DOI: 10.3390/foods11162423
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Novel and Environmentally Friendly Foods on Consumer Attitude and Behavior: A Value-Attitude-Behavioral Model

Abstract: Extreme weather conditions have intensified due to manufactured environmental damage in recent years. To reduce the environmental impact on the Earth, many consumers seek to change their dietary patterns to protect the environment and voluntarily switch to a vegetarian diet. Past studies have found that the transition from nonvegetarian to vegetarian is not easy, but promoting the consumption of alternative foods such as plant-based meat alternatives should help consumers gradually reduce their dependence on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 95 publications
1
14
0
Order By: Relevance
“…To investigate the relationship between attitudes and WTP, we included attitudes as a determinant of WTP in the model. The results in Table 4, Columns 2 and 4, show that attitude is a reliable predictor of WTP, which is consistent with previous findings (Ma and Chang, 2022; Bredahl, 2001). However, there is no heterogeneous effect of prior awareness on willingness to pay.…”
Section: Resultssupporting
confidence: 91%
“…To investigate the relationship between attitudes and WTP, we included attitudes as a determinant of WTP in the model. The results in Table 4, Columns 2 and 4, show that attitude is a reliable predictor of WTP, which is consistent with previous findings (Ma and Chang, 2022; Bredahl, 2001). However, there is no heterogeneous effect of prior awareness on willingness to pay.…”
Section: Resultssupporting
confidence: 91%
“…This has also been observed in other studies that like in Taiwan where consumers are willing to buy plant-based meat alternatives for sustainable development of the environment despite their high prices. This study concluded that consumers' perception of green value will affect their attitude toward green products (38,39). It was also suggested that that consumers who are highly concerned about animal welfare and environmental issues are likely to consider livestock meat production as causing more ethical and environmental problems than their counterparts, which may affect negatively their consumption of meat or positively their consumption of meat alternatives (40).…”
Section: Discussionmentioning
confidence: 89%
“…a . STREAMS Studies References PRINCIPAL Vgt-Vgn 92 Allen et al [ 42 .I]; Arenas-Gaitán et al [ 8 ], Aschemann-Witzel & Peschel [ 43 ]; Bagci & Olgun [ 18 ]; Boaitey & Minegishi [ 44 ]; Bobić et al [ 45 ]; Brandner et al [ 46 ]; Braunsberger et al [ 47 ]; Brouwer et al [ 48 ]; Bryant [ 49 ]; Cardello et al, [ 50 ]; Chung et al [ 51 ]; Clark & Bogdan [ 20 ]; Cliceri et al [ 3 , 52 ]; Cramer et al [ 53 ]; Crnic [ 54 ]; Estell et al [ 55 ]; Falkeisen et al [ 56 ]; Feltz et al [ 57 ]; Ghaffari et al [ 58 ]; Gili et al [ 59 ]; Graça et al [ 60 .II, 61 ]; Haas et al [ 62 ]; Hibbeln et al [ 63 ]; Hoffman et al [ 64 ]; Isham et al [ 65 ]; Judge & Wilson [ 66 , 67 ]; Kessler et al [ 68 , 69 ]; Krizanova et al [ 70 ]; Krizanova & Guardiola [ 71 ]; Larsson et al [ 72 ]; Ma & Chang [ 73 ]; MacInnis & Hodson [ 74 , 75 ]; Montesdeoca et al [ 76 ]; Moore et al [ 77 ]; Moss et al [ 78 ]; Müssig et al [ 79 ]; ...…”
Section: Resultsmentioning
confidence: 99%